Quality Assurance in Physiotherapy Education in India - Subrat Samal; Varsha Nagarkar; Shiril Nagarkar; Nitin Samal; Snehal Samal; Krishna Kumar Singh; Vaibhav P. Anjankar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: To investigate the quality assurance system in Indian physiotherapy education. Design: A crosssectional survey with mixed method was employed in this research. Participants: Forty two participantswere involved in the study and responded to a questionnaire. Seven participants out of the 42 were selectedfor video interview. Materials and Methods: A questionnaire and an audio or video interview techniquewere used for the data collection. Descriptive statistics was used to analyze the questionnaire. A qualitativemethod was analyzed with content analysis. Results: The questionnaire result showed that hardly one-thirdof participants were aware about quality in general in the physiotherapy education. In the analysis of theinterviews, four categories emerged: They indicated that awareness, skills, rating, and requirements relatedto quality seem to be important in developing quality assurance in physiotherapy. Conclusion: As a smallscale study of quality assurance system, this study can contribute to develop an overall awareness of qualitysystem in the Indian physiotherapy education. It can also contribute to the educational and professionallife ahead by developing experience and updating the upcoming new physiotherapy researches. However,affirmative effects can also extend physiotherapists in advance.